"Children of Great Development": Difficulties in the Education and Development of Rural Left-Behind Children. Issue 4 (4th July 2017) - Pan, Lu; Ye, Jingzhong
Abstract: Over the past 30 years in China, the development ideology—a model of economic development that is characterized by urbanization, industrialization, and modernization—has brought about many changes and consequences, including increased migration by the rural population, sharp adjustments in urban-rural education policy, the decline of rural society, and a deteriorating educational context facing rural left-behind children. At the family level, labor force migrations have had a far-reaching impact on left-behind children. At the school level, the decline of rural education and urbanization trend have derailed the healthy development of left-behind children. At the community level, the deterioration of rural values amid rapid urban-rural changes has aggravated the developmental risks facing left-behind children. Among rural left-behind children, those who are older (post–compulsory schooling age) and girls, and from poverty-stricken backgrounds face more developmental risks. The authors take into consideration empirical research from regions such as Sichuan and Henan, provide an account of the educational and developmental challenges facing rural left-behind children, and reflect on the developmentalist ideology underlying societal changes.